HUBUNGAN PERSONAL HYGIENE, LAMA KONTAK, DAN MASA KERJA DENGAN GEJALA DERMATITIS KONTAK IRITAN PADA PENGRAJIN TAHU MRICAN SEMARANG - Sinta Pradaningrum; Daru Lestantyo; Siswi Jayanti (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2018)
Irritant contact dermatitis is an inflammatory response unrelated to the immune reaction due to direct exposure of the irritant agent to the skin. The disease is characterized by clinical abnormalities of poliformic effluence ie edema, papule, erythema, vesicles, skuama, and itching complaints. The tofu industry Mrican Semarang is a home-based business with limited workers. The tofu production process has several steps including soaking, milling, cooking, sifting, agglomeration, molding / hardening and cutting by using acetic acid (CH3COOH). The purpose of this study is to analyze the relationship between personal hygiene, working period, and duration of contact with symptoms of irritant contact dermatitis. The type of this study is an analytic observasional with cross sectional research approach. The subjects of this study are all the workers who contact with chemicals as much as 33 people. The variable data are duration of contact, working period and personal hygiene practice are taken by interview, while practices and facilities related to Personal Hygiene with observation. Irritant contact dermatitis is determined on the basis of physical examination of the skin by the doctor. The result of chi square statistic test get the working period (p value = 0,001), duration of contact (p value = 0,001), and personal hygiene (p value = 0,026). Advice for business owners should be cooperation with the nearest health center for early and periodic checks and for workers should keep their personal hygiene from before until finish work.